The Optimum Production Equipment Scale For Open Pit Coal Mining (Society for Mining, Metallurgy & Exploration, 2004)
The trend for using larger equipment in open pit mining to achieve cost effectiveness raises the question about the optimum economic point of scale in the current world of globalization. The present paper treats this question through the prism of a new methodology of assessing the impact of the size of production equipment on the economic outcomes of coal mining ventures. The methodology incorporates a production scheduling optimization model that implements both principles of mine planning, coal quality optimization and waste deferment. The implementation of the waste deferment principle dealing with the spatial and time aspects of the mine sequence arrangement allows the adequate modeling of the optimality of production equipment scale through the use of mine investment parameters, such as, purchase and ownership costs and discounted cash flows analysis. A case study is provided to illustrate the applicability of the new methodology.